The Dynamics of Congressional Committees in Budget Legislation and Its Impact to Philippine Economic Development - Arvin Karl Demillo Capiral (Advanced Studies on Socio-Economy Development, 2023)
This research examines the dynamics of the 17th congress in the budget legislation process and posts an argument regarding its impact on Philippine economic development using a qualitative research design. The researchers use theoretical debate and literature study to identify the political motivations that affect the Congressmen in the approval of the budget, namely: self-interest, political clientelism, and political interference. An online interview was conducted with the selected key informants to know the significance of each factor in congress's decision-making regarding the budget's approval. The results indicate that self-interest, political clientelism, political interference, and the executive department significantly influence the congressional committees on the budget legislation process. This article concludes that the effectiveness of lawmakers' roles in managing the economy correlates with the majority of representation held by the government's ruling party, as in the case of the 17th congress. Keywords: Budget Legislation, General Appropriations Act (GAA), Political Clientelism, Philippine Congress